Development of a leaching procedure to assess the risk of uranium leaching due to construction and demolition waste disposal. (August 2018) - Letman, Mary Margaret; Drage, John; Ryan, Anne-Marie; Lake, Craig; Jamieson, Rob
Highlights: Construction and Demolition Waste leachate can mobilize Uranium. A new method to evaluate uranium mobilization potential is proposed. Performance of the new procedure was validated against standard leaching tests. New test is a useful tool for Construction and Demolition Waste disposal siting. Abstract: Naturally-occurring uranium can be found at elevated concentrations in groundwater throughout the world, with the potential to cause kidney damage in chronically exposed individuals. Empirical evidence shows that uranium mobilization can be enhanced in the presence of ions that are associated with leachate from construction and demolition (C&D) disposal sites. There is need for a simple and effective procedure to evaluate soil and rock formations for uranium mobility prior to the permitting of waste disposal facilities which could alter groundwater chemistry. A series of leachate extractions were performed to represent the impact of C&D leachate on uranium-bearing rocks, focusing on the impact of calcium, sodium, chloride, sulphate, and bicarbonate concentrations on uranium mobilization. Based on these observations a uranium leaching procedure (ULP) was developed and compared to the synthetic precipitation leaching procedure (SPLP). The ULP was capable of mobilizing an order of magnitude more uranium than the SPLP from six rock samples and shows promise as a tool for assessing the risk of groundwater contamination by C&D waste through uranium mobilization.